PENDIDIKAN KUNO PADA MASA MESIR DAN PERSIA - Edwin Ariwianto; Zuhdi Fahmi Firmansyah; Ulumia Hayatunnufus (Universitas Negeri Surabaya, 2017)
The purpose of making this article is to study describing ancient education in Egypt and Persia through various sources of books or research journals from experts through learning education in history through qualitative methods. Ancient education in the days of Egypt and Persia discussed a lot of knowledge ranging from mathematics, technology, chemistry, etc. Which includes learning methods and how the learning process at that time. This article is about ancient education in Egypt and Persia.Keywords: Ancient Education, Egypt, Persia